PERSEPSI ATAS SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI PADA KPP MAKASSAR SELATAN - Andi Rustam; Saida Said (Jurnal Riset Perpajakan: Amnesty, 2018)
This research aims to test the influence of Fiskus service, level of understanding and taxation of tax compliance of individual taxpayers in Makassar Pratama Selatan. The Data in this study was obtained from the taxpayer registered with the KPP Pratama Makassar Utara which was willing to become a respondent. This research uses primary data by conducting direct research in the field by providing questionnaire/question sheets to 80 respondents. The method of data analysis used is analysis of multiple linear regression. The results showed that: in partial, variable Fischus services, the level of understanding and taxation sanctions are positive and significant to the individual taxpayers ' compliance in paying taxes.  Key words:P the fiscus, the level of understanding, taxation and compliance sanctions are mandatory tax